Frustrated ambition General Vicente Lim and the Philippine Military Experience, 1910-1944 - Meixsel, Richard B. 1955- (Norman University of Oklahoma Press, 2018)
"Uses the career of Vicente Lim, the first Filipino graduate of West Point and commanding general of a Philippine Army division on Bataan during World War II, to reappraise the military history of both the Commonwealth-era Philippine Army (1936-1942) and the Philippines during the American period of occupation"--
An untiring advocate of independence : first cadet, 1910-1917 -- "A good future before you" : at home and abroad, 1917-1929 -- "Keeping down Filipino leadership" : War Plans Orange and the Filipino soldier, 1929-1934 -- "We may even be there indefinitely" : origins of the Philippine military system, 1934-1935 -- "El entusiasmo de nuestros jovenes" : implementing the military system, 1935-1939 -- "We will handle the army to suit ourselves" : changing direction, 1939-1940 -- "Nothing better to a soldier" : preparing for war, 1941 -- "The only general with cojones" : Lim on Bataan, I -- "His division, his kingdom" : Lim on Bataan, II -- "You could have stopped this useless fighting" : Bataan to Capas, February-July 1942 -- Guerrillero : the final frustration, 1942-1944.
Includes bibliographical references and index.
Keywords: Lim, Vicente -- 1888-1944.; Philippines. -- Army -- Officers -- Biography; Generals -- Philippines -- Biography; World War, 1939-1945 -- Campaigns -- Philippines; Philippines -- History -- 1898-1946.; Philippines -- History, Military -- 20th century